carebear said:
Find the quadratic whose roots are -1 and 1/3 and whose value at x = 2 is 10.
I found the equation to be p(x) = 2/3(x+1)(3x-1), which I then multiplied to get 2x^2 +4/3x-2/3 so I multiplied the entire equation by 3 to get 6x^2 + 4x - 2. However, when I check x = 2 into that equation, I do not get 10, I get 30. What am I doing wrong?
What is the correct answer?
Ok...you had p(x) = 2x[sup:v4nw6ki3]2[/sup:v4nw6ki3] + (4/3)x - (2/3)
You want the result to be 10 when you substitute 2 for x. Let's see what happens if we DO that:
p(x) = 2x[sup:v4nw6ki3]2[/sup:v4nw6ki3] + (4/3)x - (2/3)
p(2) = 2(2)[sup:v4nw6ki3]2[/sup:v4nw6ki3] + (4/3)(2) - (2/3)
p(2) = 2(4) + (8/3) - (2/3)
p(2) = 8 + (8/3) - (2/3)
8 + (6/3)
p(2) =8 + 2
p(2) = 10
It works! When you use 2 for x, you get a value of 10 for p(x)....
Now, you multiplied by 3 to get rid of the fractions, I assume. Did you remember that you need to multiply BOTH SIDES of the equation by 3?
In other words, if you have
p(x) = 2x[sup:v4nw6ki3]2[/sup:v4nw6ki3] + (4/3)x - (2/3)
and you multiply by 3, you need to multiply BOTH SIDES by 3:
3*p(x) = 3*[2x[sup:v4nw6ki3]2[/sup:v4nw6ki3] + (4/3)x - (2/3)]
3*p(x) = 6x[sup:v4nw6ki3]2[/sup:v4nw6ki3] + 4x - 2
And when you substitute 2 for x on the right side, you will, in fact, get 30....but that is (according to what is on the left side) THREE TIMES as large as the value of p(2).